PhenoWell®—A novel screening system for soil‐grown plants - Ji Li; Michael A. C. Mintgen; Sam D'Haeyer; Anne Helfer; Hilde Nelissen; Dirk Inzé; Stijn Dhondt (Plant-Environment Interactions, 2023)
Abstract As agricultural production is reaching its limits regarding outputs and land use, the need to further improve crop yield is greater than ever. The limited translatability from in vitro lab results into more natural growth conditions in soil remains problematic. Although considerable progress has been made in developing soil‐growth assays to tackle this bottleneck, the majority of these assays use pots or whole trays, making them not only space‐ and resource‐intensive, but also hampering the individual treatment of plants. Therefore, we developed a flexible and compact screening system named PhenoWell® in which individual seedlings are grown in wells filled with soil allowing single‐plant treatments. The system makes use of an automated image‐analysis pipeline that extracts multiple growth parameters from individual seedlings over time, including projected rosette area, relative growth rate, compactness, and stockiness. Macronutrient, hormone, salt, osmotic, and drought stress treatments were tested in the PhenoWell® system. The system is also optimized for maize with results that are consistent with Arabidopsis while different in amplitude. We conclude that the PhenoWell® system enables a high‐throughput, precise, and uniform application of a small amount of solution to individually soil‐grown plants, which increases the replicability and reduces variability and compound usage.